Gelatin-grafted tubular asymmetric scaffolds promote ureteral regeneration via activation of the integrin/Erk signaling pathway - Song, Baiyang; Fang, Li; Mao, Xufeng; Ye, Xianwang; Yan, Zejun; Ma, Qi; Shi, Zewen; Hu, Yiwei; Zhu, Yabin; Cheng, Yue (Frontiers in Bioengineering and Biotechnology, 2023)
The repair of diseased ureter is an urgent clinical issue to be solved. Tissue-engineered scaffold for ureteral replacement is currently insufficient due to its incompetent bioactivity, especially in long-segment abnormalities. The failure of urothelialization on scaffolds is the primary reason. In this work, we designed various porous asymmetric poly(L-lactic acid) (PLLA)/poly(L-lactide-co-e-caprolactone) (PLCL) tubes with thermally induced phase separation (TIPS) method via changing the ratio of solvents (named PP). Aiming to regulate the phenotype of urothelial cells and ureteral reconstruction, gelatin was grafted on the tubular scaffold using ammonolysis and glutaraldehyde crosslinking (named PP-gel). The hydrophilicity of the scaffold increased significantly after gelatin grafting, which promoted the adhesion and proliferation of urothelial cells. Through subcutaneous implantation into rats, PP-gel scaffolds demonstrated good biocompatibility. The results of in vivo replacement showed that PP-gel could improve urothelium regeneration and maintain renal function after the ureter was replaced by PP-gel tube with ~4 cm length, using New Zealand rabbits as the experimental animals. The related biologic mechanism of ureteral reconstruction was detected in detail. The gelatin-grafted scaffold upgraded integrin α6/β4 on the urothelial cell membrane, which phosphorylates the focal adhesion kinase (FAK) and enhances urothelialization via the MAPK/Erk signaling pathway.